Influence of perceived social support and academic self-efficacy on teacher-student relationships and learning engagement for enhanced didactical outcomes - Yaxing Wang; Lu Wang; Ling Yang; Wenwen Wang (Scientific Reports, 2024)
Abstract This research explored the link between teacher-student relationships and learning engagement, considering perceived social support as a mediator and academic self-efficacy as a moderator. A total of 930 college students completed the Academic Self-Efficacy Scale, Teacher-Student Relationships Questionnaire, Multidimensional Scale of Perceived Social Support, and College Student Learning Engagement Questionnaire. Mediating and moderating effects were investigated using SPSS19.0 and one of its process plugins 3.5. The findings indicated (1) teacher-student relationships positively predicted learning engagement; (2) perceived social support mediated the link between teacher-student relationships and learning engagement; and (3) academic self-efficacy moderated the initial phase of the pathway to the mediating role of perceived social support. Moreover, the mediating effect was more significant at elevated academic self-efficacy levels. Establishing harmonious relationships between teachers and students, nurturing students’ confidence in their academic abilities , and expanding students’ access to social support were essential to boosting the educational involvement of college students. The study findings will help educators enhance college students’ engagement in learning and provide recommendations for educators to conduct educational and teaching activities.